Two investigations into the causal link between child mortality and subsequent fertility using DHS data from Kenya, Lesotho, Malawi, Tanzania and Zimbabwe - Bungu, Manyara Lillian (Centre for Actuarial Research (CARE), 2014)
Includes abstract.